2020
DOI: 10.1097/md.0000000000020674
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of angiotensin converting enzyme inhibitors versus angiotensin II receptor blockers on insulin resistance in hypertensive patients

Abstract: Background: Previous studies have shown inconsistent outcomes in the efficacy of angiotensin-converting enzyme inhibitors (ACE inhibitors) and angiotensin receptor blockers (ARBs) on insulin resistance (IR). Hence, we aim to compare the efficacy of ACE inhibitors with ARBs on IR in hypertensive patients. Methods: Five electronic databases (included The Cochrane Library, MEDLINE, Embase, Web of Science, and Cochrane Central Register of Controlled Trials)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Contrasting with other studies [ 53 , 54 ], ARB did not change the glucose levels, yet it lowered insulin levels during the glucose challenge and ameliorated the glucose-to-insulin ratio as seen previously [ 55 , 56 ].…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…Contrasting with other studies [ 53 , 54 ], ARB did not change the glucose levels, yet it lowered insulin levels during the glucose challenge and ameliorated the glucose-to-insulin ratio as seen previously [ 55 , 56 ].…”
Section: Resultscontrasting
confidence: 51%
“…Previous studies have shown that ARBs decrease plasma glucose [ 53 , 54 ] and report improvements in insulin resistance [ 55 ], yet other studies report no changes [ 56 , 57 ]. Therefore, to better address the existing discrepancies in the literature, we measured plasma glucose and insulin statically over time and dynamically in response to the glucose load.…”
Section: Resultsmentioning
confidence: 99%
“…In previous study, statins therapy are associated with the higher risk for insulin resistance and type 2 diabetes mellitus. Fortunately, RAS inhibitors attenuate the endothelial dysfunction and risk of insulin resistance ( 21 ). In this regard, combined therapy with statins and RAS inhibitors not only demonstrates additive/synergistic effects on endothelial dysfunction and insulin resistance but also lowering cholesterol levels and blood pressure (BP) when compared with either monotherapy in patients having hypertension, hyperlipidemia ( 22 ).…”
Section: Summary Findings Of Resultsmentioning
confidence: 99%
“…The current meta-analysis with its peer-reviewed protocol published online [ 9 ] was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. INPLASY registration number was INPLASY202050032.…”
Section: Methodsmentioning
confidence: 99%